Lipid Profile Improvements: Omega-3 Fatty Acids Versus Aripiprazole as Adjuncts to Olanzapine Therapy - Ali, Farasat; Ali, Javaria Fatima; Qayyum, Muniza; Rashid, Nazia; Sajid, Aina; Uzma Qayyum (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVETo compare the beneficial effects of omega 3 fatty acids (omega 3 FA) and add on aripiprazole in patients taking olanzapine and having deranged lipid profile.STUDY DESIGNComparative study design.PLACE & DURATION OF STUDYThe study was conducted in Psychiatry department of Sir Ganga Ram Hospital (SGRH), Lahore in a duration of 6 months.METHODSixty schizophrenic patients (both genders), taking olanzapine and having deranged serum triglyceride and LDL cholesterol were recruited in two groups (Group I and Group II with 30 subjects in each group). Group I was administered 1000 mg omega 3 FA/day/oral at bed time for twelve weeks.  Group II was administered aripiprazole 5 mg /day/oral at bed time. Body weight was measured at screening and after 12 weeks. Serum triglyceride and serum LDL cholesterol of both groups were measured at screening (0 day), 6 weeks and after 12 weeks. Collected data was analyzed using SPSS 20.RESULTSAfter 12 weeks Group I showed 19% and Group II showed 15 % reduction in body weight. Group I showed 22 % reduction and Group II depicted 20 % reduction in serum triglyceride. Serum LDL cholesterol showed 20 % and 19 % reduction respectively in Group I and Group II. Body weight, serum triglyceride and LDL cholesterol of Group I and Group II had significantly (≤0.05) reduced as compared with levels at screening.CONCLUSION Treatment with omega 3 FA and aripiprazole successfully reduced body weight, serum triglycerides and LDL cholesterol.